1971
DOI: 10.1159/000152453
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme Variations in Human Cells Grown <i>in vitro</i>. VII. Subcellular Distribution of Ammo Acid Naphthylamidases

Abstract: The subcellular distribution of several isozymes of amino acid naphthylamidase was studied in HeLa cells by a combination of polyacrylamide gel electrophoresis and cell fractionation techniques. Lysosomes were detected which were fragile and lower in density than mitochondria in sucrose-water gradients. The Cu++ and Triton X-100 sensitive isozyme (A) of amino acid naphthylamidase which predominates in cells of neoplastic origin was found to be soluble. Three isozymes (the B components) were lysosomal. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results indicated that the activities against the different sub strates were inhibited to different degrees (table III). If the enzyme requiring the presence of Triton X-100 to be extracted is similarly affected, a point that we are not certain about (21), then the relative amount of enzyme in our Triton X-100 extracts would be 40-60% higher than our figures indicate. teoglycans, and a lower molecular weight frac tion (~ 230,000 daltons).…”
Section: Effect Of Triton X-100 On the Extraction Of Naphthylamidasesmentioning
confidence: 56%
“…The results indicated that the activities against the different sub strates were inhibited to different degrees (table III). If the enzyme requiring the presence of Triton X-100 to be extracted is similarly affected, a point that we are not certain about (21), then the relative amount of enzyme in our Triton X-100 extracts would be 40-60% higher than our figures indicate. teoglycans, and a lower molecular weight frac tion (~ 230,000 daltons).…”
Section: Effect Of Triton X-100 On the Extraction Of Naphthylamidasesmentioning
confidence: 56%
“…Beckman/L undgren/T arnvik The subcellular localization of the A and B isozymes in the KB cell line was studied by means of differential centrifugation according to the method described by Lundgren [1971b]. The fractions were made equal with respect to the protein concentration and examined by means of starch gel electrophoresis and subsequent staining for superoxide dismutase.…”
mentioning
confidence: 99%
“…Another possibility is that a microsomal organelle has this density. Acid phosphatase and amino acid naphthylamidase have been demonstrated in cultured HeLa cells in a mirrosomal fraction (Lundgren 1971 ) .…”
mentioning
confidence: 99%